The development of water monitoring system for IoT-based automatic aquarium - Ahmad Irfan, Ishak (2021)
Nowadays fish-keeping is become trending in world-wide communities. People from all ages like to keep gold fish for entertainment purposes, decorative or as a hobby in their homes, workplaces, mall, and hotels. There are many types of fish used for fish keeping such as marine, fresh water tropical, cold water and brackish. By depending on with what kind of fish will decide the type of water need to be used in an aquarium. But fish keeping need to take it serious action to maintain water quality such as the compatible potential of hydrogen level in water level, water turbidity level, and temperature must be in optimum condition and water level of the aquarium should always be enough to ensure the fish are in confortable and healthy condition. In additional, manual maintenance will be needed to ensure the aquarium tank is clean. For an example, water also needs to be changed and the fish needs to be fed. In this project, automatic aquarium with internet of things (IOT) application has been design to make life easier, fancier to monitor the aquarium. Most important, it able to reduce time for a hectic aquarium user. This automatic aquarium consists of the automatic water pump that already combined with filter to reduce and turbidity in the water. To monitor water quality for this aquarium, the turbidity sensor, water temperature and pH sensor reading was taken. For this project, all of these sensors will be used to measure the water quality element such as water turbidity level, pH level and the water temperature and food level. Then, the measurement value will be sending or uploaded to an application or a webserver that easily can be access in the user smartphone or browser via internet. The user able to monitor the water system to ensure water in the aquarium either in suitable condition or not based on reading value of the sensor. This automatic aquarium also will operate autonomously which trigger the mechanical part based on the requirement that had been set up. For an example, if the water temperature also did not achieve the suitable temperature for the aquarium, lamp bill be turn on to regulate the temperature inside the fish tank. Besides, if the turbidity level higher than optimum value, the motor pump will be turn on to counter the problem.